Multistrain probiotic and lactulose in the treatment of minimal hepatic encephalopathy - Ahmad Shavakhi; Huriyeh Hashemi; Elham Tabesh; Zhaleh Derakhshan; Somaye Farzamnia; Shirin Meshkinfar; Sara Shavakhi; Mohammad Minakari; Ali Gholamrezaei (Journal of Research in Medical Sciences, 2014)
Background: Some evidence has shown benefits of probiotics in the management of minimal hepatic encephalopathy (MHE). We evaluated the efficacy of a multistrain probiotic compound, alone and in combination with lactulose, in the treatment of MHE. Materials and Methods: This study has two parts. First, consecutive adult patients with MHE were randomized to receive lactulose (30-60 mL/day) + probiotic (200 million colony forming units of seven bacteria species/day) (Gp-LPr) or lactulose + placebo (Gp-L). In second part, a non-randomized group of patients received probiotic alone (Gp-Pr). Medication duration was for 2 weeks and patients were followed-up for another 8 weeks. Improvement in MHE status was assessed by psychometric hepatic encephalopathy score (PHES). Development of overt encephalopathy, hospitalization, and death were considered as secondary outcomes. Results: Sixty patients (80% male, mean age 38.4 ± 9.6 years) completed the intervention. PHES significantly improved after medication in all the three groups (Gp-LPr: −3.8 ± 3.9 to −1.6 ± 3.0; Gp-L: −4.8 ± 4.1 to −1.6 ± 2.9; and Gp-Pr: −4.9 ± 3.7 to −2.1 ± 2.5, P < 0.001). After 8 weeks follow-up, improvement was maintained in Gp-LPr and Gp-Pr, but there was deterioration in those who did not receive probiotics (Gp-L: PHES score reversed to −4.8 ± 4.2). Two patients (one each in Gp-L and Gp-Pr) experienced overt encephalopathy. One patient was hospitalized due to worsening of ascites (Gp-LPr) and one due to spontaneous bacterial peritonitis (Gp-L). Side effects were mild and not significantly different among the groups. Conclusion: Lactulose and probiotics are effective for the treatment of MHE; however, probiotics, but not lactulose, have long-term effects. More studies are required before suggesting probiotics for the standard treatment of MHE.